Altered gray matter volume in MRI-negative focal to bilateral tonic–clonic seizures - Xu, Honghao; Zhu, Haitao; Luo, Lei; Zhang, Rui (Acta neurologica Belgica, 2021)
To investigate cortical changes in MRI-negative patients with focal to bilateral tonic–clonic seizures (FBTCS). High-resolution three-dimensional T1-weighted MRI were collected with a GE 3.0-T MRI scanner from 26 patients with FBTCS and 21 healthy volunteers at Nanjing Brain Hospital. Voxel-based morphometry was performed on T1-weighted MRI of all subjects. A two-sample t test was performed to compare the GMV of two groups. Age and gender were taken as covariables, so that brain regions with significant differences, as compared by two-sample t test, between the two group were obtained. These regions were extracted as the regions of interest (ROIs) used for correlation analysis between ROIs and clinical variables. There is no significant difference in GMF between two groups. In FBTCS, regions with decreased GMV are bilateral thalamus, bilateral orbitofrontal cortex, left medical cingulate gyrus, and right supplementary motor area. GMV is increased within the bilateral para-hippocampal regions (voxel-wise FDR-corrected, P < 0.05). The GMVs are significantly negatively correlated with disease duration in the left thalamus and the left para-hippocampal region ( P < 0.05). Seizures may lead to the loss of neurons and the decrease of GMV in FBTCS. The increase of GMV in some regions might be due to inflammatory responses in the early stages of epileptic seizures.